2020
DOI: 10.1111/psyp.13743
|View full text |Cite
|
Sign up to set email alerts
|

Mutual influence between emotional language and inhibitory control processes. Evidence from an event‐related potential study

Abstract: There is abundant literature demonstrating that processing emotional stimuli modulates inhibitory control processes. However, the reverse effects, namely, how cognitive inhibition influences the processing of emotional stimuli, have been considerably neglected. This ERP study tries to fill this gap by studying the bidirectional interactions between emotional language and inhibitory processes. To this end, participants read emotional sentences, embedded in a cue‐based Go‐NoGo task. In Experiment 1, the critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…Nonetheless, this ERP effect reveals an interaction in the predicted direction, which encourages the idea that linguistic negation reuses inhibitory processes; an interpretation that is strengthened by the source-localization of the interaction at regions that are core components of the inhibitory neural network (Aron et al, 2014). Thus, there seems to be bi-directional modulations between negation and response inhibition, a finding that is generally interpreted as supporting conclusions of resource sharing between two cognitive functions (e.g., Pessoa et al, 2012;Agudelo-Orjuela et al, 2020).…”
Section: Negation Interacts With Response Inhibitionsupporting
confidence: 64%
“…Nonetheless, this ERP effect reveals an interaction in the predicted direction, which encourages the idea that linguistic negation reuses inhibitory processes; an interpretation that is strengthened by the source-localization of the interaction at regions that are core components of the inhibitory neural network (Aron et al, 2014). Thus, there seems to be bi-directional modulations between negation and response inhibition, a finding that is generally interpreted as supporting conclusions of resource sharing between two cognitive functions (e.g., Pessoa et al, 2012;Agudelo-Orjuela et al, 2020).…”
Section: Negation Interacts With Response Inhibitionsupporting
confidence: 64%
“…Beyond the processing of the motivational value of cues, this study also identified the nature of the influence of these cues on inhibition processing. Thus, the emotionally loaded appetitive and smoking-related pictures evoked a smaller early P3-NoGo (310-370 ms) than neutral pictures in both smokers and controls, a wellestablished signature of the impact of the emotional characteristics of stimuli on inhibition (Agudelo-Orjuela et al, 2021). This was followed by a smaller late P3-Go (420-470 ms), in smokers only, evoked by smokingrelated compared with neutral pictures, and only when presented from a first-person visual perspective.…”
Section: Discussionmentioning
confidence: 91%
“…Beyond the processing of the motivational value of cues, this study also identified the nature of the influence of these cues on inhibition processing. Thus, while the emotionally loaded appetitive and smoking-related pictures evoked a smaller early P3-NoGo (310 – 370) than neutral pictures in both ISH and NRS, a well-established signature the impact of the emotional characteristics of stimuli on inhibition (Agudelo-Orjuela et al ., 2021), this was followed by a smaller late P3-Go (420 – 470 ms), in ISH only, evoked by smoking-related compared to neutral pictures, and only when presented from a first-person visual perspective. Smoking-related pictures presented from a first-person visual perspective may, therefore, provoke a transient impairment of inhibitory processes associated with an automatic recruitment of the incentive motivational processes related to the influence of conditioned reinforcers on the expression of incentive habits (Belin et al ., 2013; Jones et al ., 2018).…”
Section: Discussionmentioning
confidence: 95%
“…For example, Versace et al (2011) reported more LPP of greater positive amplitudes when evoked by smoking-related, pleasant and unpleasant stimuli than those evoked by neutral stimuli. We expected to detect the motivational component of the response to cue presentation in the range of the LPP, that is, in the P3 (310 – 370 ms) taking the Go/NoGo cue as stimulus onset (Agudelo-Orjuela et al ., 2021). As anticipated, smoking-related and appetitive pictures evoked a less positive P3 (310 – 370 ms, that is 560 ms after the onset of the pictures) than neutral pictures in both ISH and NRS, thereby demonstrating that the two groups processed the emotional characteristics of the pictures similarly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation